LDOC1 inhibits proliferation and promotes apoptosis by repressing NF-κB activation in papillary thyroid carcinoma. Issue 1 (December 2015) - Zhao, Shuiying; Wang, Qingzhu; Li, Zhizhen; Ma, Xiaojun; Wu, Lina; Ji, Hongfei; Qin, Guijun
Abstract Background The incidence of thyroid cancer has progressively increased over the past few decades, and the most frequent types of this cancer are papillary thyroid carcinoma (PTC) and small primary tumors. In PTC, oncogene activation is known to occur at a high frequency. However, the potential roles of tumor suppressor genes in thyroid carcinogenesis remain unclear.LDOC1 was first identified as a gene encoding a leucine zipper protein whose expression was decreased in a series of pancreatic and gastric cancer cell lines. In this study, we aimed to determine the status of LDOC1 in PTC and identify its mechanistic role in PTC pathogenesis. Methods LDOC1 expression was evaluated in fresh samples and stored specimens of human PTC and contralateral normal tissues by performing quantitative reverse transcription-PCR and immunohistochemical staining. The correlation to nuclear p65 content in the stored specimens was analyzed. Moreover, the basal level of LDOC1 in two human PTC-derived cell lines (BCPAP and TPC-1) compared with normal thyroid tissue was determined. HumanLDOC1 cDNA was inserted into a lentiviral vector and transduced into TPC-1 cells. TPC-1 cells overexpressing LDOC1/GFP (Lv-LDOC1) or negative control GFP (Lv-NC) were stimulated with TNFα or recombinant TGF-β1, and then cell proliferation, cell cycle distribution, and apoptosis were assessed. Western blotting was used to examine the expression of p65, IκBα, c-Myc, Bax, and Bcl-xL, and a luciferase reporter assay was used to measure NF-κB activity stimulated by TNFα. Statistical significance was determined using Student'st tests or ANOVA and Newman-Keuls multiple comparison tests. Pearson chi-square test was used to analyze possible associations. Results LDOC1 expression was significantly downregulated in PTC specimens as compared with the expression in normal thyroid tissues, and this downregulation was associated with an increase in tumor size (P  < 0.05). There is a correlation between LDOC1 and nuclear P65 expression in human PTC tissues (P  < 0.01). Lentivirus-mediated restoration of LDOC1 expression in TPC-1 cells characterized by low level of LDOC1 expression suppressed proliferation and induced apoptosis by inhibiting NF-κB activation, and LDOC1-overexpressing TPC-1 cells recovered responsiveness to TGF-β1 antiproliferative signaling. Conclusions LDOC1 might function as a tumor suppressor gene in PTC by inhibiting NF-κΒ signaling, and thus might represent a promising therapeutic target in patients with PTC.